The Sum and Product of Independence Numbers of Graphs and their Line Graphs (Journal of Informatics and Mathematical Sciences, 2014)
The bounds on the sum and product of chromatic numbers of a graph and its complement are known as Nordhaus-Gaddum inequalities. In this paper, we study the bounds on the sum and product of the independence numbers of graphs and their line graphs. We also provide a new characterization of the certain graph classes.
Keywords: Independence number; Matching number; Line graph